Review of Hypertension Management at University of South Florida BRIDGE Clinic - Atkinson, Brian; Uichanco, Lauren; Kattih, Zein; Perera, Yohan; Angell, Erin; Uhlar, Courtney; Martinez, Valeria; Roetzheim, Alex; Lopez, Jesus; Guerra, Lucy; Gonzalez, Eduardo (Journal of Student-Run Clinics, 2018)
Background: Hypertension is one of the most prevalent diseases in the United States, and proper disease management is essential in preventing multi-system organ damage. The BRIDGE Healthcare Clinic is a student-run free clinic that cares for a primarily uninsured, immigrant population in Tampa, Florida. This retrospective study aimed to assess the quality of hypertension management provided at BRIDGE Clinic and compare our hypertension outcomes with the 8th Joint National Committee (JNC8) guidelines and national rates of blood pressure (BP) control. Methods: Chart reviews of all patients seen at BRIDGE Clinic from May 1, 2012 to May 1, 2017 were performed. Patients with hypertension, defined by JNC8 as a previous diagnosis of hypertension, a BP >140/90 mmHg for patients <60 years old, or BP >150/90 for patients >60 years old, on â‰¥2 occasions, were included in the study. Information collected included patient demographics (age, race, gender, body mass index, comorbidities), BP at initial visit, BP at most recent visit, total number of visits, dates of initial and most recent visits, and types of antihypertensive medications being used. Data were analyzed using SPSS statistics software. Results: Of the 599 patients reviewed, 97 patients (between the ages of 29 and 89 years) were found to have a diagnosis of hypertension per JNC8 criteria. Compared to the national average of 53%, 55.7% of BRIDGE Clinic had BPs at goal (defined as BP <140/90 in patients <60 years old, and BP <150/90 in patients >60 years old). There was also a significant decrease in systolic BP by 10.9 mmHg (p<0.0001, 95% confidence interval [CI] 6.9-14.9 mmHg) and diastolic BP by 5.4 mmHg (p<0.0001, 95% CI 3.3-7.5 mmHg) from initial visit to most recent visit. Conclusions: As a student-run free clinic dependent on volunteers and donors, BRIDGE Clinic has been able to achieve clinically and statistically significant decreases in BP, along with rates of BP control that are comparable to national averages for both insured and uninsured Americans.